2021
DOI: 10.33584/rps.17.2021.3450
|View full text |Cite
|
Sign up to set email alerts
|

Modelling perennial ryegrass (Lolium perenne) persistence and productivity for the Upper North Island under current and future climate

Abstract: The objective of this study was to predict the future performance of perennial ryegrass in the Upper North Island, New Zealand. The Basic Grassland model, BASGRA, was used with historic, current and future daily climate data as input, and soil water holding capacity, to predict changes in perennial ryegrass performance in space and time. The study focussed on land of ≤7° slope north of the town of Tokoroa and considered two potential warming pathways to the end of the 21st century. Persistence was defined as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
2
10
1
Order By: Relevance
“…3 0 M a y 1 8 2 7 S e p 1 8 2 5 J a n 1 9 2 5 M a y 1 9 2 2 S e p 1 9 2 0 J a n 2 0 1 9 M a y 2 0 1 6 S e p 2 0 1 4 J a n 2 1 1 4 M a y 2 1 1 1 S e p 2 1 0 9 J a n 2 2 Total unsown species (% of total DM) There was a strong seasonal trend in perennial ryegrass performance and a loss of ryegrass persistence characterised by weed ingress, regardless of heading date. This is consistent with research in the upper North Island of New Zealand, in which perennial ryegrass populations declined and the abundance of weedy species increased as pastures aged (Tozer et al 2014;Dodd et al 2018;Beukes et al 2021).…”
Section: Establishment Of Treatments and General Trendssupporting
confidence: 90%
“…3 0 M a y 1 8 2 7 S e p 1 8 2 5 J a n 1 9 2 5 M a y 1 9 2 2 S e p 1 9 2 0 J a n 2 0 1 9 M a y 2 0 1 6 S e p 2 0 1 4 J a n 2 1 1 4 M a y 2 1 1 1 S e p 2 1 0 9 J a n 2 2 Total unsown species (% of total DM) There was a strong seasonal trend in perennial ryegrass performance and a loss of ryegrass persistence characterised by weed ingress, regardless of heading date. This is consistent with research in the upper North Island of New Zealand, in which perennial ryegrass populations declined and the abundance of weedy species increased as pastures aged (Tozer et al 2014;Dodd et al 2018;Beukes et al 2021).…”
Section: Establishment Of Treatments and General Trendssupporting
confidence: 90%
“…Compared with the late flowering diploid group, fewer mid‐season heading diploids were commercialized in the 2000s though the release of Request in 2011 indicates renewed interest (albeit with little evidence of progress compared with older mid‐season types). This is timely, given the trend toward warmer winters and hotter drier summers in the upper North Island during the 2010s (Glassey et al, 2021) signalling possible future climates for this region under which summer and autumn pasture growth will be constrained (Beukes et al, 2021; Keller et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is not known if the traits required to deal with intensifying climate and pest pressure on ryegrass in the upper North Island (Beukes et al, 2021; Mansfield et al, 2021) can be found within the accessions of Lolium and Epichloë currently being used in New Zealand breeding programmes. Other accessions that have not come through in commercial material to‐date (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now indisputable that some combinations of local climate and soil type, often exacerbated by insect pest damage, present environments that are beyond the adaptive range of current perennial ryegrass cultivars (Lee et al 2017;Jagger 2021;. The specific environmental combinations, and the lethal factors operating, are still poorly defined although simulation tools are being developed to help address this knowledge gap (e.g., Beukes et al 2021). Perennial ryegrass is generally able to withstand, and recover from, single stress events like a drought, overgrazing, or insect damage (Chapman et al 2011) but multiple simultaneous stresses can collectively exceed thresholds of plant survival (Cullen et al 2006;Tozer et al 2017;Moot et al 2021).…”
Section: Job Security: Pasture Persistence Adaptation and Resiliencementioning
confidence: 99%